PROFIL KONDISI FISIK PEMAIN SEPAK BOLA SSB PANDAWA SALATIGA U-13 TAHUN 2026 - Joko Sanyoto; Setiyawan Setiyawan; Yulia Ratimiasih (YLPK Mahardhika, 2026)
The purpose of this research is to determine the physical condition profile of the SSB Pandawa Salatiga U-13 football players in 2026. This research uses a cross-sectional quantitative descriptive approach. The research subjects consisted of 20 players from SSB Pandawa Salatiga who were 13 years old. The data collection method consists of examination and measurement of physical condition, which includes strength, flexibility, agility, speed, and endurance. The results were analyzed using descriptive statistical analysis, which presented the data in the form of percentages and categorization based on T-scores. The research findings indicate that most players fall into the moderate category, with 9 players (45%) in this category, 8 players (40%) in the less category, 2 players (10%) in the good category, and 1 player (5%) in the very poor category. The average VO?Max value of the players was 45.54 with a standard deviation of 4.00, a maximum value of 51.25, and a minimum value of 34.44. The results show that the physical condition of the SSB Pandawa Salatiga U-13 players in 2026 is generally in the moderate category. Therefore, to improve the players' performance, more systematic and sustainable physical training is needed.